2017
DOI: 10.1038/s41598-017-15861-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide contributes to high-salt perception in a blood-sucking insect model

Abstract: In all organisms, salts produce either appetitive or aversive responses depending on the concentration. While low-salt concentration in food elicits positive responses to ingest, high-salt triggers aversion. Still the mechanisms involved in this dual behavior have just started to be uncovered in some organisms. In Rhodnius prolixus, using pharmacological and behavioral assays, we demonstrated that upon high-salt detection in food a nitric oxide (NO) dependent cascade is activated. This activation involves a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…Based on morphological studies by means of scanning electron microscopy, eight taste sensilla were identified in the anterior part of the pharynx of R. prolixus 36,49 . Likely, these sensilla are responsible for the gustatory evaluation of blood, following biting and sucking a gorge of blood in kissing bugs 36,[56][57][58] . However, electrophysiological studies are necessary to corroborate their function as, for example, bitter-sensitive GRNs tuned to alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Based on morphological studies by means of scanning electron microscopy, eight taste sensilla were identified in the anterior part of the pharynx of R. prolixus 36,49 . Likely, these sensilla are responsible for the gustatory evaluation of blood, following biting and sucking a gorge of blood in kissing bugs 36,[56][57][58] . However, electrophysiological studies are necessary to corroborate their function as, for example, bitter-sensitive GRNs tuned to alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Host skin recognition by taste receptors, as well as that of blood taste properties, has been shown to be relevant for skin piercing and feeding in these bugs [30,31]. The identification of the receptors underlying the molecular bases of NaCl, KCl and ATP recognition, three of the main signals mediating the evaluation of skin and blood quality features, is yet to be revealed.…”
Section: -Chemoreceptionmentioning
confidence: 99%
“…For example, low-salt (< 0.1 M) triggers insect feeding and oviposition, whereas high-salt (> 0.1 M) promotes avoidance and prevents egg-laying (3)(4)(5)(6)(7)(8)(9). Salts are detected by the taste system, a sensory modality that helps animals make predictions about the value of a potential food source, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in most animals studied so far, the assessment of salt concentration drives acceptance or avoidance behavioral responses (1, 2). For example, low-salt (< 0.1 M) triggers insect feeding and oviposition, whereas high-salt (> 0.1 M) promotes avoidance and prevents egg-laying (39). Salts are detected by the taste system, a sensory modality that helps animals make predictions about the value of a potential food source, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation